Are risk predicting models useful for estimating survival of patients with rheumatoid arthritis-associated interstitial lung disease? - Nurmi, Hanna M. (BMC Pulm Med, 2017)
BACKGROUND: Risk predicting models have been applied in idiopathic pulmonary fibrosis (IPF), but still not validated in patients with rheumatoid arthritis-associated interstitial lung disease (RA-ILD). The purpose of this study was to test the suitability of three prediction models as well as individual lung function and demographic factors for evaluating the prognosis of RA-ILD patients. METHODS: Clinical and radiological data of 59 RA-ILD patients was re-assessed. GAP (gender, age, physiologic variables) and the modified interstitial lung disease (ILD)-GAP as well as the composite physiologic indexes (CPI) were tested for predicting mortality using the goodness-of-fit test and Cox model. Potential predictors of mortality were also sought from single lung function parameters and clinical characteristics. RESULTS: The median survival was 152 and 61 months in GAP / ILD-GAP stages I and II (p = 0.017). Both GAP and ILD-GAP models accurately estimated 1-year, 2-year and 3-year mortality. CPI (p = 0.025), GAP (p = 0.008) and ILD-GAP (p = 0.028) scores, age (p = 0.002), baseline diffusion capacity to carbon monoxide (DLCO) (p = 0.014) and hospitalization due to respiratory reasons (p = 0.039), were significant predictors of mortality in the univariate analysis, whereas forced vital capacity (FVC) was not predictive. CPI score (HR 1.03, p = 0.018) and baseline DLCO (HR 0.97, p = 0.011) remained significant predictors of mortality after adjusting for age. CONCLUSIONS: GAP and ILD-GAP are applicable for evaluating the risk of death of patients with RA-ILD in a similar manner as in those with IPF. Baseline DLCO and CPI score also predicted survival.